Analyzing India's coal, natural gas, and biomass energy consumption: Evidence from a Fourier technique to promote sustainable development - Eweade, Babatunde Sunday; Joof, Foday; Adebayo, Tomiwa Sunday (John Wiley and Sons Inc, 2025)
Inalignment with the United Nations Sustainable Development Goals (UN-SDGs),which pinpoint vital aspects such as SDG-7 and SDG-8, this study delves intothe impact of biomass energy on economic growth in the Indian context. It alsoconsiders the roles of fossil fuels, specifically natural gas and coal. Toaccomplish this, a comprehensive analysis is initiated, making use of annualdata spanning from 1975 to 2022. A unique Fourier ARDL test serves as a centralanalytical tool alongside the Fourier Toda Yamamoto test. The empirical resultsunveil the presence of co-integration among the variables scrutinized. Moreover,it becomes evident that coal and biomass make positive contributions toeconomic growth, whereas natural gas appears to exert a negative influence oneconomic growth. To validate these findings, a Fourier-based Toda-Yamamoto testis applied, demonstrating that natural gas, coal, and biomass possesspredictive capabilities concerning economic growth. These discoveries carrysubstantial implications for comprehending the factors influencing economicgrowth in India. © 2024 United Nations.
Keywords: Biomass energy consumption; Coal consumption; Economic Growth; Fourier ARDL technique; India; Natural gas consumption